The Use of RAFT Strategy in Teaching Writing Personal Letters at SMAN 3 Kisaran - Harahap, Ihdini Sabila; Lis Supiatman; Dalila Haini (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
This study aims to describe the use of the RAFT (Role, Audience, Format, Topic) strategy in teaching personal letters to eleventh-grade students at SMA N 3 Kisaran. Many students often face difficulties in starting their writing, expressing ideas, and organizing content in a personal letter. The RAFT strategy is used to help students write from a specific perspective, focus on the intended audience, and follow the correct format. This descriptive qualitative research was conducted through observation, student writing analysis, and interviews. The results showed that RAFT helped students generate ideas more easily, improved the structure and relevance of their letters, and increased their engagement during writing activities. Students also reported that the strategy made the task more meaningful and enjoyable. Therefore, the RAFT strategy can be considered an effective alternative to support students' writing skills in personal letter texts.